Eco-friendly and Economical Spectrophotometric Estimation of the Low Water-Soluble Drug (Norfloxacin) Applying the Concept of Mixed Hydrotropy - Soni, Ketan; Sharma, Kavita (Journal of Health and Allied Sciences NU, 2021)
Objectives The main aim of the research was to analyze an economical and eco-friendly approach to improve the solubility of norfloxacin. The current analysis was to utilize the hydrotropic solutions to extract the drugs from their dosage forms, avoiding the use of costlier and harmful organic solvents.Materials and Methods In this study, an ultraviolet–visible spectrophotometer (model 1800, Shimadzu Corporation) was used to analyze the norfloxacin drug. The mixed hydrotropy approach was used to determine the solubility of norfloxacin. In this work, a blend solution (20% of urea + 20% of sodium benzoate) was used as a hydrotropic solubilizing agent.Results The solubility of norfloxacin drug in water was very low at ∼0.88 mg/mL and the solubility of norfloxacin drug in the blend solution was 11 mg/mL. From 98.96 (tablet II) to 99.35 (tablet I), the percent estimation value was achieved. This value was nearly 100, so the proposed method was correct. Standard deviation (0.2540–0.4156), percentage coefficient of variation (0.2566–0.4183), and the value of standard error (0.1481–0.2415) are also very low; hence, we can say that the proposed method is accurate.Conclusion To avoid the use of organic solvents, the mixed hydrotropy concept can be used for spectrophotometric estimation of low water-soluble drugs from bulk drug samples. It provides an economical and environmentally friendly mechanism.
Keywords: norfloxacin; mixed hydrotropy; estimation; solubility; sodium benzoate